Energy balance, GHG emission and economy for cultivation of high biomass verities of bamboo, sorghum and pearl millet as energy crops at marginal ecologies of Gujarat state in India. (April 2020) - Patel, Beena; Patel, Akash; Gami, Bharat; Patel, Pankaj
Abstract: This study was carried out to explore biomass variety of sorghum, pearl millet and bamboo for second generation biofuel feedstock production at salinity and drought prone marginal land at three districts of Gujarat state, India. The biomass feedstock under study were compared with the native crop varieties for its economic sensitivity as well as native varieties of the same crops for energy and carbon dioxide equivalent (CO2 eq) greenhouse gas (GHG) emission. Net income per matric tone of harvested biomass sorghum, pearl millet and bamboo were 52.02 USD, 20.37 USD and 124.66 USD respectively which is economically profitable as compared to native sorghum and pearl millet varieties. Bamboo showed highest net income of 8 USD/day based on the annual land occupancy which is double than biomass sorghum. Positive net energy balance of 454.29 GJ/Ha/crop cycle, 278.20 GJ/Ha/crop cycle and 602.49 GJ/Ha/Year were found for biomass sorghum, pearl millet and bamboo respectively. GHG emission was positive and lowest for bamboo 42.55 KgCO2 eq/MT as compared to biomass sorghum 48.97 KgCO2 eq/MT and pearl millet 74.53 CO2 eq/MT. Cost benefit analysis revealed that bamboo has highest net income, lowest GHG emission, highest net energy balance and highest biomass production per USD spent among the other biomass crops. Highlights: Energy crops for biofuel production are accepted but strives for land availability. High biomass sorghum, pearl millet & bamboo were studied as energy crop. High biomass bamboo showed highest economic, energy & environment benefits. Bamboo plantation in multicrop system may be applied by integrated policy support.